Effect of Morinda citrifolia fruit powder on physiological and productive performance of Cavia porcellus - Paredes-López, Daniel Marco; Robles-Huaynate, Rizal Alcides; Beteta-Blas, Xiomara; Aldava-Pardave, Uriel (Frontiers in Veterinary Science, 2023)
The breeding of guinea pig is part of the pluriactivity for millions of farming families in rural areas from the Peruvian Andean and Amazonian regions and other South American Andean countries. Rearing these specie plays an important source of employment, income, and nutrition for millions of rural families on these countries. The search of natural products for enhancing animal wellbeing, health, and production and thereby of guinea pigs is being searched nowadays. The aim of this study was to determine the effect of the ripe fruit powder of Morinda citrifolia on the physiological and productive performance parameters of reared guinea pigs under humid tropical conditions and to find a new use of noni fruit and to improve the guinea pig as an agrifood product. For this purpose, forty-eight male Peru breed guinea pigs sixty days old, were used and distributed into four treatments with diets containing 0, 2, 4 and 8% of the noni ripe fruit powder, with four replicates and 3 guinea pigs each. Erythrocytes, hematocrit, hemoglobin profiles, hematological indices MCV (mean cell volume), MCHC (mean corpuscular hemoglobin concentration), MCH (mean corpuscular hemoglobin) and blood metabolites profiles: TP (total protein), ALB (albumin), GLO (globulin), TC (total cholesterol) were determined. The productive performance indices: DWG (daily weight gain), DCFI (daily concentrated feed intake), TFIFM (total feed intake of fresh matter) and TFIDM (total feed intake of dry matter), FRCFM (feed rate conversion for fresh mater) and FRCDM (feed rate conversion for dry matter) were evaluated. The guinea pigs were evaluated at 60, 75 and 90 days old. The interaction between noni fruit powder and the age of guinea pigs produced an increase in the erythrocyte, hematocrit, MCH and MCHC levels at 75 days old, (p < 0.05). The final weight and the daily weight gain increased, while the feed rate conversion for fresh and dry matter decreased, as the level of noni fruit powder in the diet increased until 4% (p < 0.05). Thus, the level of noni ripe fruit powder in the guinea pigs' diets had a positive effect on the erythrocyte, leucocytes, hematocrit, MCH, MCHC levels, the final weight, the daily weight gain, and the feed rate conversion of fresh and dry matter.